A Glimmer in the Darkness of Totalitarianism: The Attempt to Research International Relations in the Period of Reform Communism (Czech Journal of International Relations, 2002)
This paper deals with the relation between the study of International Relations (IR) and political power in Communist Czechoslovakia, specifically focusing on the latter half of the 1960s.This relation is theoretically interpreted with help from the concept of logos/polis, which analytically explains the relation of recognition and power. For empirical analysis, the work relies primarily on the research activity of the former Institute for International Politics and Economics (IIPE), especially the quarterly journal it published, called International Relations (with which this publication is associated). Though the research of IR was firmly subordinate to political decision-making and did not have the prerequisite conditions in which to develop independently for nearly the entire totalitarian period, with the exception of a few months in 1968, a number of the researchers of this period still endeavored to establish the new discipline of IR. These scholars were well aware that only through establishing an independent discipline for the research of IR could they free themselves from the political and ideological imperatives restricting their freedom to study and prohibiting them from endorsing any standpoint other than the official party line.For a short time the political dynamics did enable conditions for the formation of the discipline and for the consideration of other alternatives to Czechoslovak foreign policy. This was, however, merely a fleeting success that was later crushed by the August invasion.